Desenvolvimento de estratégias para a determinação espectrofotométrica sequencial em fluxo de Co (II) e Mn (II) - Ferreira, Juliana Aparecida (2009)
In this study a kinetic-spectrophotometric method was developed for sequential determination of Co and Mn in pharmaceutical samples. The method was based on the catalytic effect of the analytes in the oxidation reaction of Tiron by H2O2 in basic medium. In the case of Mn it was employed the activator reagent 2,2-bipyridine to effective catalysis. The FIA system was projected taking into account the catalytic properties of each analyte in the indicator reaction. Two factorial designs were applied, initially, a fractionary factorial design 29-5 followed by a complete factorial design 23 to select the important variables, and then a factorial design 22 + central point + star for optimizing of FIA system. Fractionary factorial designs 27-2 were applied in the study of possible interferents for Co and Mn. The main interferents were mathematically described using factorial + central point + star designs. The pharmaceutical samples were digested by concentrated HNO3 in digestor block. To evaluate the accuracy of the developed method, samples (n=3) were analyzed by FS-FAAS and based on the determination concentrations, these were diluted to posterior analysis aplyingby the developed method. Limits of detection (LOD) and quantification (LOQ) for FS-FAAS were 3.9 and 13.2 μg L-1 for Co; 110.0 and 366.0 μg L-1 for Mn, respectively. To developed method the LOD and LOQ were 0.055 and 0.18 μg L-1 for Co, 9.76 and 32.5 μg L-1 for Mn, respectively. Comparison between the two methods was evaluated by paired t-test. At 99% confidence level, the values did not differ statistically for Co. However, for Mn, the concentration values agreed but this data cannot be statistically confirmed due to differences of standard deviations of the two methods. The repeatability was 3.2% for Co and 8.0% for Mn. The sampling frequency was 25 samples h-1.